2011
DOI: 10.3109/17435390.2011.625132
|View full text |Cite
|
Sign up to set email alerts
|

In vitroeffect of CTAB- and PEG-coated gold nanorods on the induction of eryptosis/erythroptosis in human erythrocytes

Abstract: Gold nanorods (Au-NRs) have attracted enormous interest due to their size and unique optical properties. Many studies have demonstrated their use in biomedical systems. However, their potential toxicity is not fully understood. This study evaluated the effects of the Au-NRs (15 nM × 64 nM) coated with CTAB (cetyltrimethylammonium bromide) or PEG (polyethylene glycol) in human erythrocytes on the induction of haemolysis and erythroptosis. In our study, erythroptosis (also known as eryptosis) was determined syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
160
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(161 citation statements)
references
References 34 publications
1
160
0
Order By: Relevance
“…The characteristic absorbance spectrum was scanned for hemoglobin released from erythrocytes upon the treatments with different concentrations of C‐GNRs (Figure 1B, bottom panel). Based on the absorbance at 541 nm, the hemolysis ratio was quantitatively calculated and the results showed that the positively charged nanoparticles exerted higher hemolytic activity than the negatively charged ones, and the pure erythrocytes in PBS were more vulnerable to nanorod stimulation than those in whole blood (Figure 1C), which was similar to the previous finding 12. Additionally, hemolysis of erythrocytes induced by C‐GNR was instant (within 0.2 h), nevertheless exhibited in time‐dependent and concentration‐related manners (Figure 1D and Figure S2, Supporting Information).…”
Section: Resultssupporting
confidence: 86%
“…The characteristic absorbance spectrum was scanned for hemoglobin released from erythrocytes upon the treatments with different concentrations of C‐GNRs (Figure 1B, bottom panel). Based on the absorbance at 541 nm, the hemolysis ratio was quantitatively calculated and the results showed that the positively charged nanoparticles exerted higher hemolytic activity than the negatively charged ones, and the pure erythrocytes in PBS were more vulnerable to nanorod stimulation than those in whole blood (Figure 1C), which was similar to the previous finding 12. Additionally, hemolysis of erythrocytes induced by C‐GNR was instant (within 0.2 h), nevertheless exhibited in time‐dependent and concentration‐related manners (Figure 1D and Figure S2, Supporting Information).…”
Section: Resultssupporting
confidence: 86%
“…In analogy to apoptosis of nucleated cells, erythrocytes may enter eryptosis, the suicidal death of erythrocytes characterized by cell shrinkage [45] and cell membrane scrambling with phosphatidylserine exposure at the cell surface [46]. Cellular mechanisms involved in the triggering of eryptosis include increase in cytosolic Ca 2+ activity ( [Ca 2+ ] i ) [46], ceramide [47], oxidative stress [46], energy depletion [46] and activated caspases [46,48,49]. Eryptosis is further stimulated following activation of casein kinase 1a, Janus-activated kinase JAK3, protein kinase C and p38 kinase [46].…”
mentioning
confidence: 99%
“…Increased [Ca 2+ ] i further leads to phospholipid scrambling of the cell membrane with phosphatidylserine translocation to the erythrocyte surface [11]. Eryptosis is further stimulated by ceramide formation [13], caspase activation [14][15][16][17][18] and deranged activities of AMP-activated kinase AMPK [19], casein kinase 1a [20,21], cGMP-dependent protein kinase [15], Janus-activated kinase JAK3 [22], protein kinase C [23], p38 kinase [24], PAK2 kinase [25], sorafenibsensitive kinases [26] and sunitinib-sensitive kinases [27]. Eryptosis is elicited by a wide variety of xenobiotics [13,, including tannic acid [48], honokiol [62], gossypol [46], gambogic acid [63], tanshinone II A [47], apigenin [64], ursolic acid [65], thymoquinone [66], oridonin [67] and a-lipoic acid [14].…”
mentioning
confidence: 99%